Ecological responses of the endemic anole, Anolis bicaorum, to rapid habitat degradation on Utila Island, Honduras - Brown, Thomas W. (2020)
The genus Anolis is composed of over 400 New World lizards belonging to the family Dactyloidae. The high diversity and rate of endemism in this group has attracted a foray of research, but the population status of many species remain unassessed and their ecological responses to anthropogenic changes unknown. My study set out to generate the first population estimates for Anolis bicaorum, a little known anole endemic to Utila Island, Honduras. The study compiled an extensive occurrence, abundance, morphological and ecological dataset from which to test various hypotheses around sexual dimorphism, and the effect of declining population density. During the course of study, my survey sites were impacted by varying degrees of disturbance, such as fire, deforestation and human traffic. I repeated the surveys to provide an updated population estimate from which to compare annual status and determine if abundance had declined in response to habitat degradation. In summary, my key results include 1) plotting the distribution and apparent habitat preferences of A. bicaorum using occurrence-based data, 2) demonstrating a significant trend of population decline in response to anthropogenic disturbance, and 3) identifying a significant reduction in sexual-size dimorphism in response to disturbance driven population declines. Overall my data advise that A. bicaorum be considered as Critically Endangered in accordance with IUCN Redlist Criteria, but continued research is needed to monitor future changes in its conservation status.